2023
DOI: 10.1021/jacs.2c13677
|View full text |Cite
|
Sign up to set email alerts
|

Bifunctional Electron-Transporting Agent for Red Colloidal Quantum Dot Light-Emitting Diodes

Abstract: Indium phosphide (InP) quantum dots have enabled light-emitting diodes (LEDs) that are heavy-metal-free, narrow in emission linewidth, and physically flexible. However, ZnO/ZnMgO, the electron-transporting layer (ETL) in high-performance red InP/ ZnSe/ZnS LEDs, suffers from high defect densities, quenches luminescence when deposited on InP, and induces performance degradation that arises due to trap migration from the ETL to the InP emitting layer. We posited that the formation of Zn 2+ traps on the outer ZnS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 28 publications
1
3
0
Order By: Relevance
“…Panels b and c of Figure illustrate the adsorption energy ( E ads ) and defect passivation between the QD and dipole molecules. The previous reports showed that zinc vacancies (V Zn ) and sulfur vacancies (V S ) have lower defect formation energy than sulfur interstitials (S int ), and zinc interstitials (Zn int ), which are two dominant defects in ZnS, indicating S atoms and Zn atoms are exposed on the (111) ZnS surface. , The X-ray diffraction (XRD) plots of QD in Figure S3 confirmed the shell of QD is consistent with a zinc blende structure of ZnS Figure S4 illustrates E ads of QD and OA ligands.…”
supporting
confidence: 68%
“…Panels b and c of Figure illustrate the adsorption energy ( E ads ) and defect passivation between the QD and dipole molecules. The previous reports showed that zinc vacancies (V Zn ) and sulfur vacancies (V S ) have lower defect formation energy than sulfur interstitials (S int ), and zinc interstitials (Zn int ), which are two dominant defects in ZnS, indicating S atoms and Zn atoms are exposed on the (111) ZnS surface. , The X-ray diffraction (XRD) plots of QD in Figure S3 confirmed the shell of QD is consistent with a zinc blende structure of ZnS Figure S4 illustrates E ads of QD and OA ligands.…”
supporting
confidence: 68%
“…To alleviate this issue, we introduce pentafluoro­benzenethiol (PF-BT) at the interface between NiO and the QDs to facilitate the hole injection. This molecule serves as a dipole layer, effectively downshifting the VBE of the NiO film by 0.25 eV, accompanied by the passivation of nonstoichiometric Ni states (Ni 3+ ). Consequently, the QD-LED now exhibits an enhanced peak current efficiency of 1.7 cd/A (Figure S2).…”
Section: Resultsmentioning
confidence: 99%
“…The bifunctional ETL successfully passivated Zn 2+ traps and prevented migration between layers, leading to a 1.4-fold EQE improvement compared to traditional ZnMgO controls. 104 Minh-Son Hoang et al addressed phase separation in a hybrid poly(9,9-dioctylfluorene- alt-N -(4-sec-butylphenyl)-diphenylamine) (TFB) and polyvinylcarbazole (PVK) system used as a HTL for QLEDs. Without phase separation, the hybrid HTL significantly improved QLED performance, reducing turn-on voltage by approximately 47% and increasing brightness by around 37%.…”
Section: Photophysical Properties Of Cqdsmentioning
confidence: 99%